Bioaccumulation and biomagnification in elasmobranchs: A concurrent assessment of trophic transfer of trace elements in 12 species from the Indian Ocean. (November 2021) - Boldrocchi, G.; Spanu, D.; Mazzoni, M.; Omar, M.; Baneschi, I.; Boschi, C.; Zinzula, L.; Bettinetti, R.; Monticelli, D.
Abstract: We provided the first multi-species study investigating the presence and organotropism of trace elements in three tissues of 12 elasmobranch species. Shark species showed comparable TE loads, although milk sharks and juvenile scalloped hammerhead sharks exhibited the highest Cd and Hg levels, respectively. Fins accumulated higher levels of Pb, Co, and Cr; muscles higher V, As, and Hg; livers higher Se and Cd levels. The organotropism of TEs calls for cautious when choosing a tissue to be sampled since certain tissues, like fin clips, do not provide reliable surrogate for the internal loads of some TEs. Strong correlations between essential and toxic TEs indicated detoxification mechanisms, while the TMF provided evidence for Hg, As and Se biomagnification along the food-web. Considering the difficulties in assessing elasmobranchs contamination from different areas, the proposed multi-species approach represents a valuable way to estimate the species-specific accumulation and transfer of pollutants in sharks. Graphical abstract: Unlabelled Image Highlights: TEs were quantified in fin, muscle and liver of 12 elasmobranchs from Djibouti. Higher Pb, Mn, Co, Cr levels in fins; As and Hg in muscles; Se and Cd in livers Tissue-specific TEs loads call for cautious in the choice of tissues to be sampled. Correlations between essential and toxic TEs indicated detoxification mechanisms. TMF provided evidence for the biomagnification of Hg, As and Se along the food-web.